2020
DOI: 10.21037/cdt.2020.01.13
|View full text |Cite
|
Sign up to set email alerts
|

Carotid plaque imaging profiling in subjects with risk factors (diabetes and hypertension)

Abstract: Carotid artery stenosis (CAS) due to the presence of atherosclerotic plaque (AP) is a frequent medical condition and a known risk factor for stroke, and it is also known from literature that several risk factors promote the AP development, in particular aging, smoke, male sex, hypertension, hyperlipidemia, smoke, diabetes type 1 and 2, and genetic factors. The study of carotid atherosclerosis is continuously evolving: even if the strategies of treatment still depends mainly on the degree of stenosis (DoS) dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 111 publications
(170 reference statements)
0
18
0
2
Order By: Relevance
“…Several studies used ultrasound to detect the rupture-prone atherosclerotic plaque and the tissue characterization of such plaque for the prevention of future cardiac events[ 205 - 207 ]. Furthermore, studies have used ultrasound-based imaging techniques for CVD risk assessment in patients with diabetes[ 187 - 189 , 191 , 193 , 195 , 196 , 208 - 212 ] and, thus, could also be adopted for diabetic patients with COVID-19. Several other imaging-based studies have shown the interaction of plaque measurements in diabetes patients[ 196 , 211 , 212 ].…”
Section: Role Of Atherosclerosis Imaging In Diabetes Patients During mentioning
confidence: 99%
“…Several studies used ultrasound to detect the rupture-prone atherosclerotic plaque and the tissue characterization of such plaque for the prevention of future cardiac events[ 205 - 207 ]. Furthermore, studies have used ultrasound-based imaging techniques for CVD risk assessment in patients with diabetes[ 187 - 189 , 191 , 193 , 195 , 196 , 208 - 212 ] and, thus, could also be adopted for diabetic patients with COVID-19. Several other imaging-based studies have shown the interaction of plaque measurements in diabetes patients[ 196 , 211 , 212 ].…”
Section: Role Of Atherosclerosis Imaging In Diabetes Patients During mentioning
confidence: 99%
“…Hypertension is an important risk factor for clinical cardiovascular events. A study [ 44 ] on carotid arteries found that increases in both systolic and diasotlic blood pressure were associated with a range of plaque components, including IPH. Hypertension also affected vessel wall volume and fibrous cap.…”
Section: Discussionmentioning
confidence: 99%
“…Carotid and femoral atherosclerotic plaque burden is a surrogate marker for CVE, which is increased in individuals with high CVD risk [24,[26][27][28][29]. The carotid and femoral ultrasound examination in all study participants were performed using GE Vivid (Vivid E9 Ultrasound System, GE Healthcare), equipped with a linear probe-type M12L (5.6-14 MHz), as presented in our previous study [30].…”
Section: Ultrasound Image Acquisitionmentioning
confidence: 99%